The relationship between reading methods and learning styles in comprehending English texts among upper secondary students of SMK Simunjan No.1 / Marlisa Othman - Othman, Marlisa (2015)
The purpose of the study was to determine the relationship between two types of reading methods (reading aloud and silent reading) and two types of learning styles (visual and auditory) to reading comprehension of upper secondary students of SMK Simunjan No.l. Descriptive statistics was used to collect the intended data. 120 upper secondary students were selected to be part of this study. Their learning styles of the students were identified prior to dividing them into two groups: the Oral Reading Group and Silent Reading Group. A learning style inventory and IELTS Reading Text were employed in this study. The learning style inventory was used to identify the students' learning styles whereas the IELTS Reading Test were used to test the students' reading comprehension. The data was then analyzed using Independent Sample T-test and Factorial ANOVA. The findings showed that Oral Reading Group scored better in the reading comprehension test than Silent Reading Group. The auditory learners in Oral Reading Group had higher score in reading comprehension test than those in Silent Reading Group. On the other hand, visual learners obtained slightly higher score in Oral Reading Group than those in Silent Reading Group. However, the data did not show any significance relationship between reading methods and learning styles in students' reading comprehension. This study helped the teachers to create awareness of the importance of getting know of their students' learning styles prior to planning an effective lesson. By practicing suitable methods that match with students' learning styles, it will enable both teachers and students to produce a better outcome in teaching and learning process, particularly in reading lesson for language classroom.